Cross-Domain Energy Savings by means of Unified Energy Agents - Linnenberg, Tobias; Derksen, Christian; Fay, Alexander; Unland, Rainer (Industrial Agents, 2015)
This chapter presents a novel approach to dynamic resource allocation in hybrid energy grid scenarios, called energy-agents. This concept allows the easy control of inter-domain energy exchanges, such as heat generation from electricity or gas, the production of gas from electricity, or vice versa, based on the first law of thermodynamics. In a first hardware and software implementation, we were able to showcase the functionality and usability of this approach, enabling the developers of smart grid solutions to use the same code throughout the entire development process. This reusability will help to keep down development time and costs. On top of this, we were able to realize energy and cost savings by dynamically allocating the energy sources, as required by the consumer processes.